Improvement of tax policy of territorial communities in the context of budget decentralization - Korytko, Tetyana; Kruk, Olena (Technology audit and production reserves, 2018)
The object of research is the process of improving tax policy at the level of territorial communities, taking into account the specifics of fiscal decentralization. One of the most problematic places is the redistribution of tax revenues between levels of the budget system. The existing division doesn’t contribute to stimulating local governments to mobilize and search for sources to increase their own economic resources for the implementation of social programs and increase the investment activity of the territorial community. Improving tax policy is associated with the need to increase the level of fiscal independence of local governments. The analysis of the current state of revenues of state and local budgets in terms of the formation of the corporate income tax, as well as financial results and the level of profitability of operating activities by types of industrial activity of enterprises is carried out. Based on the extrapolation method, a forecast of the amount of the corporate income tax is made. The structure of the redistribution of corporate income tax between the levels of the budget system is determined. The introduction of the structure of the redistribution of corporate income tax between the levels of the budget system is hampered by the lack of a systematic decentralization process. A systematic approach, methods of analysis and synthesis, and an extrapolation method to predict the amount of tax on corporate profits are used. The main directions of improving tax policy at the level of territorial communities in the context of fiscal decentralization are identified. This ensures the possibility of increasing the investment activity of enterprises located within a certain territorial community. Compared with the existing structure of the distribution of corporate income tax between the levels of the budget system, the proposed approach allows to provide incentives for local authorities to search for sources of enhancing their own economic resources to implement social programs. As well as increasing the investment activity of the territorial community.